Meningkatkan Hasil Belajar Siswa Kelas X SMK Materi Eksponen Menggunakan Model E-Learning Dengan Aplikasi Googlemeet - Iffah, Jauhara Dian Nurul; Purna, Bagas Satria (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2024)
The background of this research is the low mathematics learning outcomes of class X TPm students due to the fact that when learning students are less active in participating in mathematics learning. The learning model that can be applied to overcome this problem is the E-Learning model. The purpose of this research is to increase the activity and learning outcomes of class X TPm students. This research method uses observation and tests. The instruments used were student activity observation sheets and student learning outcomes tests. The research was conducted by class X TPm SMK Kusuma Negara Mojoagung with a total of 15 male students. The results of observing student activities by applying the E-Learning model cycle I reached 74.44%, the criteria were moderate and increased in cycle II by 78.3%, the criteria were High. Classical completeness of student learning outcomes in cycle I, 73.33% increased in cycle II to 80%. So, this research shows that there is an increase in the activity and results of learning mathematics for class students at SMK Kusuma Negara Mojoagung by applying the E-Learning model